A Systematic Review of Human Bat Rabies Virus Variant Cases: Evaluating Unprotected Physical Contact with Claws and Teeth in Support of Accurate Risk Assessments. - Virginia M Dato; Enzo R Campagnolo; Jonah Long; Charles E Rupprecht (PLoS ONE)
In the United States and Canada, the most recent documented cases of rabies have been attributed to bat rabies viruses (RABV). We undertook this systematic review in an effort to summarize and enhance understanding of the risk of infection for individuals who have been potentially exposed to a suspect or confirmed rabid bat. United States rabies surveillance summaries documented a total of 41 human bat-rabies virus variant verified non-transplant cases between 1990 and 2015. All cases were fatal. Seven (17.1%) of 41 cases reported a bite from a bat. Ten (24.3%) cases had unprotected physical contact (UPC); these included seven cases that had a bat land or crawl on them (contact with claws) and one case that touched a bat's teeth. Seven (17.1%) cases had probable UPC. Insectivorous bat teeth are extremely sharp and highly efficient for predation upon arthropod prey. Bats also have sharp claws on the end of their thumbs and feet. One of the most common bat RABV variants has an ability to replicate in non-neural cells. Questioning individuals about unprotected contact with bat teeth and claws (including a bat landing or crawling on a person) may help identify additional exposures.